Analisis Hukum Pidana Mati Pasca Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana Dalam Penegakan Hukum Dan Hak Asasi Manusia - Abdurrahman Saleh; Vherry Andora; Irlan, Irlan (Lex Stricta : Jurnal Ilmu Hukum, 2026)
In criminal law, the death penalty is one of the most controversial forms of punishment because it lies at the intersection of law enforcement, legal certainty, and the protection of human rights. The legal framework governing the death penalty in Indonesia underwent significant changes following the enactment of Law No. 1 of 2023. The death penalty is no longer considered a principal punishment; it is now regarded as a special punishment subject to a specific probationary period. This study examines the reorientation of criminal law policy regarding the death penalty following the enactment of Law No. 1 of 2023 from the perspectives of legal certainty and human rights. This normative legal research was conducted using legislative, conceptual, and analytical methodologies. The research findings indicate that a more selective, restrictive, and precautionary model has emerged from the legal policy shift regarding the death penalty in the Criminal Code. Through the application of more systematic norms, these regulations enhance legal certainty and facilitate the protection of human rights through probationary periods, assessments of the convicted person’s behavior, and the possibility of converting the death penalty to life imprisonment. Therefore, the reorientation of the death penalty following Law No. 1 of 2023 demonstrates the legislature’s effort to balance the interests of public protection, legal certainty, and respect for human dignity.